Effects of different drumsticks on drum sound production: A case study of UiTM Shah Alam students / Muhammad Faiz Othman - Othman, Muhammad Faiz (2014)
The study was carried out to educate beginner and student drummers regarding the knowledge of effect of different drumsticks on drums sound production. The objective of this research is to explain and provide guidelines for beginner and student drummer me proper way to choose drumsticks that suitable with genre of music that they ate playing. This study will also find solution that drummers face regarding the effect of the sound from drumsticks. Lastly, this research will then find the suitable drumsticks for every drummer in genre that they are playing.